2020
DOI: 10.32602/jafas.2020.002
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acquisition Synergy on Firm Perfomance moderated by Firm Reputation

Abstract: This study was conducted to examine the impact of the operating synergy, financial synergy and firm reputation toward firm performance in merger and acquisition processes. This study also examines how firm reputation moderates the impact of operating synergy and financial synergy toward firm performance. The object of this research are companies involved in mergers and acquisitions between 2010 and 2016. Design/methodology/approach: The purposive sampling method is used to select the research sample. The descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
2
1
Order By: Relevance
“…This impact is significant so increased corporate reputation will enhance firm performance. This findings supported the previous studies of Sayilir and Victor (2019), Edi et al (2020), and Haleblian et al (2017. The findings specifically revealed that from the business perspective, corporate reputation is increasingly important for businesses for sustainable development, particularly in the context of increasingly fierce competition pressure because of international integration of the world economy and trade.…”
Section: Discussion Of the Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This impact is significant so increased corporate reputation will enhance firm performance. This findings supported the previous studies of Sayilir and Victor (2019), Edi et al (2020), and Haleblian et al (2017. The findings specifically revealed that from the business perspective, corporate reputation is increasingly important for businesses for sustainable development, particularly in the context of increasingly fierce competition pressure because of international integration of the world economy and trade.…”
Section: Discussion Of the Resultssupporting
confidence: 93%
“…The concept of CSR became popular in the 1950s when Bowen (1953) urged entrepreneurs to contribute to community development through company policies. It was followed by Manne & Wallich (1972); Beyer (1972); Drucker (1974) and Carson (1977), and many businessmen, leaders, consumer advocacy organizations and environmental activists, are strong advocates of the concept of social responsibility. The social responsibility's concept assumes that businesses are generating money from using the natural resources directly or indirectly and this affects natural resources over time; moreover, the large-scale and continuous production of corporations also damages the environment and the ecosystem.…”
Section: Corporate Social Responsibility (Csr) Measuresmentioning
confidence: 99%
“…Small acquisitions, on the other hand, result in both operating and financial benefits for investors. To sum up, our findings contradict the popular belief that operating synergy is much easier to obtain for huge firms than financial synergy (Basri & Arafah, 2020; Devos et al, 2009; Kwilinski et al, 2019, 2020; Ogada et al, 2016;). We argue that because large deals are synonymous with premiums, their uncertainty makes it more unlikely to have any financial benefits.…”
Section: Conclusion and Policy Implicationscontrasting
confidence: 99%
“…A recent investigation by Hamidlal and Harymawan (2021) demonstrates a favorable association between the CEO's expert power and organisational performance. Recent study by Basri & Arafah (2020) suggest that companies might choose experienced, competent, and aggressive CEOs in Indonesia to optimise their reputation and performance. Li and Singal (2017) indicate that CEO characteristics like experience retain substantial connections with business profitability in publicly listed hospitality companies in North America as a sample.…”
Section: Discussionmentioning
confidence: 99%